International out-migration from Gujarat, India: the magnitude, process and consequences. (2nd September 2017) - Bhagat, R.B.; Das, K.C.; Prasad, Rajiva; Roy, T.K.
Abstract : India is known for sending a large number of indentured labour to Africa and Caribbean to work in sugar cane and plantation agriculture during the colonial rule. However, the emigration to the West started after the Second World War, more specifically after 1965, as a result of the liberalisation of immigration policy of US and other western countries. Also, emigration to the Middle East increased rapidly since late1970s as a result of oil boom. Of late, there has been an increase in unskilled and semi-skilled labour emigration from many states of India. Historically Gujarat has been one of the leading states in emigration from of India. It is believed that Gujaratis migrated abroad to work as traders, businessmen, shopkeepers, hoteliers, professionals etc. A comprehensive study of Gujarati emigration which includes the characteristics of emigrants, the individual and household strategies, the process of migration comprising of formal (recruitment agency) and informal channels (family, kin, friends, religious groups and NGOs) of migration, costs and financing of migration, the contact, visits and remittances sent by the migrants to their native households would be helpful in understanding the causes and consequences of migration from Gujarat. This study makes an attempt to study Gujarati emigration in the recent past based on a household survey of about 10, 000 households conducted in 2012. It estimates the level of emigration, the characteristics and process of emigration and decision-making, remittances sent and utilized. It also assessed the impact of emigration at the household and community levels.